Demonstrating the reliability of in vivo metabolomics based chemical grouping: towards best practice - Mark R. Viant; E. Amstalden; T. Athersuch; M. Bouhifd; S. Camuzeaux; D. M. Crizer; P. Driemert; T. Ebbels; D. Ekman; B. Flick; V. Giri; M. Gómez-Romero; et al. (Archives of Toxicology, 2024)
While grouping/read-across is widely used to fill data gaps, chemical registration dossiers are often rejected due to weak category justifications based on structural similarity only. Metabolomics provides a route to robust chemical categories via evidence of shared molecular effects across source and target substances. To gain international acceptance, this approach must demonstrate high reliability, and best-practice guidance is required. The MetAbolomics ring Trial for CHemical groupING (MATCHING), comprising six industrial, government and academic ring-trial partners, evaluated inter-laboratory reproducibility and worked towards best-practice. An independent team selected eight substances (WY-14643, 4-chloro-3-nitroaniline, 17α-methyl-testosterone, trenbolone, aniline, dichlorprop-p, 2-chloroaniline, fenofibrate); ring-trial partners were blinded to their identities and modes-of-action. Plasma samples were derived from 28-day rat tests (two doses per substance), aliquoted, and distributed to partners. Each partner applied their preferred liquid chromatography–mass spectrometry (LC–MS) metabolomics workflows to acquire, process, quality assess, statistically analyze and report their grouping results to the European Chemicals Agency, to ensure the blinding conditions of the ring trial. Five of six partners, whose metabolomics datasets passed quality control, correctly identified the grouping of eight test substances into three categories, for both male and female rats. Strikingly, this was achieved even though a range of metabolomics approaches were used. Through assessing intrastudy quality-control samples, the sixth partner observed high technical variation and was unable to group the substances. By comparing workflows, we conclude that some heterogeneity in metabolomics methods is not detrimental to consistent grouping, and that assessing data quality prior to grouping is essential. We recommend development of international guidance for quality-control acceptance criteria. This study demonstrates the reliability of metabolomics for chemical grouping and works towards best-practice.

P22-44: In vitro – in vivo comparison of read-across approaches for phenoxy herbicides based on metabolome data from rat plasma and HepG2 cells - G. Caroline; F.M. Zickgraf; V. Giri; V. Haake; B. Birk; S. Sperber; H.-A. Huener; A. Verlohner; P. Driemert; T. Walk; D. Funk-Weyer; H. Kamp (Toxicology Letters, 2023)